(untitled) (Research, Society and Development, 2022)
This study aims to identify symptoms of anxiety, depression, and stress in multi-professional residents of a public hospital. In this descriptive and cross-sectional survey, 60 residents from eight health specialties responded to the Depression Anxiety and Stress Scale. It was found that 93.3% were women, of an average 25 years of age. The participants’ average level of anxiety was classified as moderate and the levels of depression and stress were classified as mild. A difference was perceived between first-year (R1) and second-year (R2) residents, with the average of R2 being higher than that of R1 regarding anxiety, depression and stress. Almost all (98.3%) stated they had already felt stressed during their residency, with "workload" being the most cited stressor. Half of them said they had thought about giving up residence, with "physical and emotional exhaustion" being the most frequent reason. The most cited coping strategy was “meditation / breathing exercises”.